Diaspora on display: a semiotic exploration of minangkabau visual identity in warung makan padang ampera across jawa - Gema Ariprahara; Sunarmi; Handriyotopo (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study examines how Minangkabau cultural identity is visually constructed and negotiated through the storefront displays of Warung Makan Padang Ampera (WMPA) in Java’s rantau (migration) context. Using a qualitative multi-site design, we documented 60 WMPA storefronts in Bandung, Yogyakarta, and Malang through systematic photography and field notes, complemented by photo-elicitation interviews with owners. Visual data were analyzed using Barthes’ tri-level semiotic framework (denotation, connotation, and myth) to identify recurrent signs and the cultural narratives they stabilize. The findings reveal a consistent set of identity anchors marawa color codes, Minangkabau roofline (gonjong) icons, and open paluang/stacked-plate showcases while typography, façade composition, and material treatments adapt to local urban constraints and market positioning. Beyond mapping recurring elements, the study argues that WMPA visual branding functions as a model of vernacular modernity, where recognizability is secured through stable anchors while urban viability is achieved through flexible, street-level adaptation. The significance of these findings lies in extending cultural branding and vernacular aesthetics scholarship from corporate and heritage settings to everyday micro-entrepreneurial foodscapes, showing how cultural identity and trust cues are maintained and recalibrated in ordinary commercial environments. Methodologically, this research contributes by operationalizing Barthes’ tri-level analysis for food-stall storefronts, offering a replicable protocol for interpreting visual identity in informal urban commerce.